Radicular Cyst associated with Deciduous Molar: A Clinical Case Report - Limbu, Senchhema; Vaidya, Subhani; Dikshit, Parajeeta; Malla, Manisha (Journal of Nepalese Association of Pediatric Dentistry, 2022)
An association of radicular cyst with deciduous teeth is very rare contributing to 0.5–3.3% of the total number of cysts in deciduous dentition in 3–19 years of age. This paper describes the case of a radicular cyst associated with deciduous molar in a 9-year-old female patient, with a detailed description of clinical, radiographic, histopathologic features, and its surgical management. The treatment included complete enucleation of the cyst with proper curettage, extraction of the offending deciduous molar and preservation of the permanent tooth buds.